Berberine encapsulated nanoparticles stimulate osteoblast differentiation in vitro - Minh, Nguyen Thi Hong; Tuan Anh, Tran; Thuy Duong, Le Thi; Viet Linh, Nguyen; Phuong, Nguyen Thi Mai (Vietnam Journal of Biotechnology, 2021)
Berberine has been known as a traditional component for treatment of intestinal-related diseases in Asian countries. Additionally, it possesses a variety of pharmacological properties, which were studied for treating tumor, diabetes, cardiovascular disease, hyperlipidemia, inflammation, bacterial and viral infections, cerebral ischemia trauma, and mental disease. Moreover, berberine has been known as an anti-osteoporotic agent by controlling both osteoclast (bone resorption cells) and osteoblast (bone-forming cells) functions. Beside the beneficial effects of berberine, it has some drawbacks that hindered its applications and resulted in low bioavailability. One of the most drawback characteristics of berberine is that it has poor watery solubility. To overcome these limits, nanotechnology has been used as the primary approach to deliver berberine in different nano-formulations. In this study, a novel berberine nanoparticle (nanoberberine, NBB) with good water dispersion was synthesized to enhance its bioavailability. The result showed that NBB was successfully developed in spherical shape and approximately 559 nm of mean size. Besides, in vitro release study revealed that berberine content release from NBB was 3 to 4 times higher than that from free berberine. Moreover, no cytotoxicity was observed for both NBB and berberine on osteoblast MC3T3-E1 cells at the tested concentrations. Additionally, alkaline phosphatase (ALP) activity, a marker for osteoblast differentiation process, was significantly higher in NBB compared to free berberine at the same test concentrations. This result indicated that NBB could be a potential biological agent for inducing bone formation. Overall, our data indicated that NBB could improve bioavailability, especially osteogenesis activity in vitro compared to free berberine.